Pengaruh Permainan Playmat dengan Keterampilan Motorik Anak Tunagrahita Ringan - Melindah, Melindah; Mawardah, Mutia (Universitas Muhammadiyah Metro, 2023)
This study aims to determine the effect of playmat games on the motor skills of mild mentally disabled children at SLB-C YPAC Palembang. The data source in the form of primary data was obtained from the playmat game scale and motor skills. The sample in this study was mentally disabled children aged 10 to 14 years who were still active at SLB-C YPAC Palembang, totalling 11 people. Data analysis used quantitative analysis using one group pretest-posttest design. Based on the hypothesis test ( paired sample t-test), the average pretest motor skill score was 46.33. As for the posttest score, the average value of motor skills is 68.00, and the probability value is sig. (2-tailed)=0.000 then p < 0.05, p < 0.01. data: So, there is a difference between motor skills in the pretest and posttest, which means that the playmat significantly influences motor skills in mentally disabled children aged ten to fourteen years at SLB-C YPAC Palembang. There are playmat activities; children become more active and excited. Playmats are effective for attracting children's attention in learning and improving motor skills because they are considered interesting and easy to do. They can arouse enthusiasm for learning to achieve targeted indicators of fine and gross motor achievement for children.